Penggunaan Sport Card berbasis Augmented Reality untuk Meningkatkan Pemahaman Siswa dalam Pembelajaran Bola Voli - Synthiawati, Novita Nur; Zen, M. Zaim; Ningrum, Dwi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to analyze the impact of using Sport Cards based on Augmented Reality (AR) on students’ understanding in volleyball learning. A quantitative approach was employed using a pre-experimental design in the form of a one-group pretest-posttest model. The participants were 27 sixth-grade students at MI Hasyim Asy’ari. A cognitive test was utilized as the research instrument to assess students’ conceptual understanding. The findings revealed an increase in the average score from 61.37 in the pretest to 84.44 in the posttest. The results of the paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference before and after the intervention. These results demonstrate that AR-based Sport Cards are effective in enhancing students’ understanding of basic volleyball techniques and show strong potential for the integration of interactive technology in physical education.